EFEKTIVITAS PENGEMBANGAN MODUL BIMBINGAN KLASIKAL UNTUK KESADARAN DIRI PESERTA DIDIK KELAS VIII SMP FK BINA MUDA - Aulia, Vita; Fatimah, Siti; Manuardi, Ardian Renata (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2023)
Development of modules as a medium of innovation in guidance and counseling activities, especially in classical guidance services. This module is used as teaching material for service materials that are focused on the context of learners' self-awareness. This research uses an R&D method developed by Borg and Gall which was adapted to stage seven. The purpose of this study is to produce a product that has been tested by several experts such as material experts, media experts, and practitioner experts. The research subjects consisted of 39 students at SMP FK Bina Muda who were specially selected to measure product feasibility through modules. Based on the product testing results that have been obtained from several experts and the response of students, this module has an average percentage of 9 1.63% according to the criteria that this product is very feasible to use for the Junior High School level.  Meanwhile, the results of the t-test analysis on the pretest and posttest result data were obtained by sig. (2-tailed) by 0.000. Thus, the results of the research on the effectiveness of this analysis showed that there was a positive change between the use of modules and the self-awareness of class VIII students at SMP FK Bina Muda.